2022
DOI: 10.1039/d1dt03546k
|View full text |Cite
|
Sign up to set email alerts
|

A novel cyclic dinuclear gold(i) complex induces anticancer activity via an oxidative stress-mediated intrinsic apoptotic pathway in MDA-MB-231 cancer cells

Abstract: A new dinuclear cyclic gold(I) complex [Au2(DCyPA)2](PF6)2, 1 based on bis[2-(dicyclohexylphosphano)ethyl]amine (DCyPA) has been synthesized and characterized by elemental analysis, IR and NMR spectroscopies, and X-ray crystallography. In the dinuclear...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Furthermore, we have recently shown that the cyclic gold(I) complex of bis[2-(dicyclo-hexylphosphano)ethyl]amine showed an effective anticancer response against the triple-negative breast cancer cells (MDA-MB-231), which was mediated via oxidative stress-mediated activation of intrinsic apoptosis. 14 Here, we speculate that exposure to complexes 1-4 may proceed through similar mechanisms that are associated with the disruption of the DC m and potential activation of the intrinsic apoptotic pathway. It is worth mentioning that other mechanisms of toxicity cannot be ruled out.…”
Section: Mitochondrial Potential Assaymentioning
confidence: 70%
See 4 more Smart Citations
“…Furthermore, we have recently shown that the cyclic gold(I) complex of bis[2-(dicyclo-hexylphosphano)ethyl]amine showed an effective anticancer response against the triple-negative breast cancer cells (MDA-MB-231), which was mediated via oxidative stress-mediated activation of intrinsic apoptosis. 14 Here, we speculate that exposure to complexes 1-4 may proceed through similar mechanisms that are associated with the disruption of the DC m and potential activation of the intrinsic apoptotic pathway. It is worth mentioning that other mechanisms of toxicity cannot be ruled out.…”
Section: Mitochondrial Potential Assaymentioning
confidence: 70%
“…In the IR spectra of the complexes (1-4), the n(P-C) bands of phosphane ligands were observed around 1100 cm À1 and 1000 cm À1 . 14,15 The n(CQC) modes of the aromatic ring were detected at about 1470 cm À1 . The medium intensity bands in the region of 2900 cm À1 in the IR spectra are assigned to n(C-H)(aliphatic) vibrations, while those above 3000 cm À1 represent the aromatic C-H stretches.…”
Section: Synthesis and Spectroscopic Characterizationmentioning
confidence: 99%
See 3 more Smart Citations